The Correlation Between Food Insecurity Level and Stunting in Indonesia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
Indonesia is among the five countries with the highest burden of stunting. Food insecurity reflecting the availability of food in the household is one of the indirect causes of undernutrition. This study examines the relationship between food insecurity and stunting in Indonesia. We used data from the 2021 Indonesian Nutrition Status Survey (SSGI) with a sample size of 82,777 under-five children selected using multistage random sampling. The relationship between food insecurity and stunting was calculated using cox regression to obtain crude and adjusted prevalence ratios (PR) considering strata and weights. Children from households with moderate food insecurity had a (PR unadj) 1.24 (1,18 – 1,31) times higher risk of stunting, and the risk rose in households with severe food insecurity (PR unadj) 1.39 (1,27 – 1,53). Subgroup analysis based on regional categories showed that the association between food insecurity and stunting was only significant in rural areas. Children in rural regions who experienced moderate food insecurity had a 1.09 (95% CI 1.02-1.16) times greater risk of stunting and an increased risk of 1.15 times (95% CI 1.03 – 1.28) in households with severe food insecurity. Interventions are needed to prevent stunting by improving household food security, particularly in rural areas. Further research is needed with better study designs to prove a causal relationship between food insecurity and stunting.